Pengaruh Good Corporate Governance dan Profitabilitas Terhadap Financial Distress - Pingkan Septa Aulia; Suwandi Suwandi (Universitas Muhammadiyah Gresik, 2023)
This research aims to determine the effect of Good Corporate Governance and Profitability on Financial Distress. The method used in this research is quantitative with secondary data in the form of complete annual financial reports of the company. The population of this study is property and real estate companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The research sample amounted to 48 companies using purposive sampling technique. Data analysis using Partial Least Square (PLS) analysis with the help of Smart-PLS 3 software. The results of this study indicate that Good Corporate Governance with the proxy of the Board of Directors, Audit Committee, Board of Commissioners and Profitability with the proxy of ROA, ROE, ROI have an effect on Financial distress.